1980
DOI: 10.1002/food.19800240911
|View full text |Cite
|
Sign up to set email alerts
|

Study of the spinnability of emulsions based on a two‐phase water‐casein‐sodium alginate system

Abstract: The spinnability of emulsions basing on a two-phase water-casein-sodium alginate system (pH 7.2) was studied as a function of the compositions of the co-existing phases and of the ratio of their volumes by measuring the maximum fiber take-up velocity. It has been established that the spinnability of the emulsion is practically independent of the compositions of the co-existing phases. The dependence of the spinnability of the emulsion on the ratio of the volumes of the phases can be illustrated by an S-shaped … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

1985
1985
2008
2008

Publication Types

Select...
6
1

Relationship

3
4

Authors

Journals

citations
Cited by 11 publications
(3 citation statements)
references
References 6 publications
(4 reference statements)
0
3
0
Order By: Relevance
“…Investigations of several systems containing albumins and neutral polysaccharides have revealed a limited thermodynamic compatibility (TDC) of proteins with polysaccharides (Grinberg and Tolstoguzov, 1972). Based on the microrheology of model two-phase liquid systems, it has been suggested that they could be used to generate fibers and form anisotropic gels without spinnerets (Tolstoguzov et al, 1973;Antonov et al, 1980;Suchkov et al, 1980).…”
Section: Thermodynamic Compatibility Of Proteins Withmentioning
confidence: 99%
See 1 more Smart Citation
“…Investigations of several systems containing albumins and neutral polysaccharides have revealed a limited thermodynamic compatibility (TDC) of proteins with polysaccharides (Grinberg and Tolstoguzov, 1972). Based on the microrheology of model two-phase liquid systems, it has been suggested that they could be used to generate fibers and form anisotropic gels without spinnerets (Tolstoguzov et al, 1973;Antonov et al, 1980;Suchkov et al, 1980).…”
Section: Thermodynamic Compatibility Of Proteins Withmentioning
confidence: 99%
“…The spinnability studies of emulsions based on twophase casein-sodium alginate-water systems (Suchkov et al, 1980) have demonstrated that spinnability is very dependent on the phase composition and volume ratio (Figure 14). Away from the phase inversion point, emulsion spinnability is governed by the spinnability of the dispersion medium, i.e., by the continuous matrix phase, whereas in the phase inversion region, the spinnability switches from one constant value to another.…”
Section: Thermodynamic Compatibility Of Proteins Withmentioning
confidence: 99%
“…Typically, the resulting fibers (∼100 μm) are coagulated in baths containing acid and salt solutions, and then washed. Hydrocolloids, such as carrageenan , and alginate, , or vegetable proteins, such as soy or field bean protein, were used in combination with casein in a two-phase blend to decrease the solubility in water of the casein-based fibers produced. In the case of spun pea and fababean protein, fibers with a granular core and strand-like cortex were formed .…”
Section: Introductionmentioning
confidence: 99%